Determination of physiochemical properties of raw honey samples - Beykaya, Mehmet (Progress in Nutrition, 2021)
Honey is a natural food produced by honey bees from nectar of flowers and the secretion of plants caused by certain insects. It has been well-known for its nutritional and medicinal values since ancient times. In this study, 60 honey samples (cotton, citrus, Astragalus, lavender, jerusalem thorn, flower, cedarwood, pine, chesnut and nigella sativa) were collected from different locations and determined their physicochemical properties like hydroxy methyl furfural (HMF), proline, sugar content, invertase, diastase number, moisture, acidity, color and electric conductivity (EC). In all honey samples, glucose and fructose are present in approximately equal proportions. The color of cotton honey is the lightest one. The acid amounts of honeys were ranged between 13.0-34.0 meq/kg. The proline content of the honey samples used in this study varied between 404.2-881.7 mg/kg and the HMF content was varied between 2.5 mg/kg and 12.3 mg/kg according to honey types. Enzymes are one of the quality criteria for the raw honey. Diastase number of honey samples was determined between 6.35 and 18.6 DN and amount of invertase enzyme ranged from 103.3 to 378.1 U/kg. In this study, physicochemical properties of raw honey samples which were collected from different regions were determined. Thus, this systematic study provides a fundamental knowledge of raw honey quality.